2020
DOI: 10.1007/s00204-020-02919-8
|View full text |Cite
|
Sign up to set email alerts
|

Chronic cardiac structural damage, diastolic and systolic dysfunction following acute myocardial injury due to bromine exposure in rats

Abstract: Background: Highly reactive halogens such as bromine are more commonly utilized, leading to an increase in quantities that are stocked and transported, therefore increasing the risk of accidental or deliberate exposure. Here we describe progression and potential mechanisms of adverse effects of a single injurious insult on the heart caused by bromine inhalation. Our studies have shown that bromine inhalation causes acute myocardial ischemia-reperfusion-like injury mediated by cytosolic calcium overload and inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Using a rat model, our studies have shown that a single dose of acute Br 2 exposure causes decreased heart rate, cardiac hypertrophy, increase in cardiac injury markers in blood, and increased ultrastructural damage [1,2]. We also demonstrated that the cardiac damage was caused by the presence of increased brominated fatty acids and aldehydes in the heart along with bromination of cardiac sarco(endo)plasmic reticulum calcium-ATPase (SERCA) and cardiac phosphalamban dephosphorylation that further decreased SERCA activity.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Using a rat model, our studies have shown that a single dose of acute Br 2 exposure causes decreased heart rate, cardiac hypertrophy, increase in cardiac injury markers in blood, and increased ultrastructural damage [1,2]. We also demonstrated that the cardiac damage was caused by the presence of increased brominated fatty acids and aldehydes in the heart along with bromination of cardiac sarco(endo)plasmic reticulum calcium-ATPase (SERCA) and cardiac phosphalamban dephosphorylation that further decreased SERCA activity.…”
Section: Introductionmentioning
confidence: 83%
“…Interestingly, most of these effects persisted till 28 days of observation in the model and resulted in increased right ventricular (RV) and LV end-diastolic pressure and LV end-diastolic wall stress with increased LV fibrosis. The LV dysfunction in this model at this delayed duration was accompanied by SERCA inactivation that resulted potentially from increased oxidative stress, as shown by increased myocardial hydroxynonenal accumulation and increased NADPH oxidase-2 (Nox-2) [1]. SERCA2 inactivity could also be attributed to a striking loss of phosphalamban (PLN) phosphorylation that started 24 h after Br 2 inhalation and persisted at 7, 14, and 28 days after exposure.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations